Tamblingan to be A Spiritual Tourism Destination - I Made Ari Kapela (Bali Tourism Journal, 2020)
Buleleng regent, Putu Agus Suradnyana confirmed Tamblingan will be promoted as a spiritual tourism object. the plan was a request from pengrajeg catur desa or four villages leader on Tamblingan Lake vicinity. The Lake status as a sacred site, has been preserved since the 10th century. The ancient Tamblingan communities erected many holy shrines nearby. They are Dalem Tamblingan temple, Endek temple, Ulun Danu temple, Sang Hyang Kangin temple, and Sang Hyang Kawuh temple. Then Gubug Temple, Tirta Mengening Temple, Naga Loka Temple, Pengukiran Temple, Pengukusan, Batulepang Temple, Embang temple and Tukang Timbang temple. Despite its status as holy site, Tamblingan Lake acts as sanctuary to various types of vegetation and wild animals. The regental government realized the byproduct possibilities of promoting new tourism object is land conversion. Tourist area status often invites high-scale business investors to establish supporting facilities around the site, which can adversely affect the lake habitat's sustainability. to minimise further exploitation, Agus Suradnyana encourages indigenous villages to compose pararem (customary rules) in the villages around Lake Buyan and Tamblingan. The regulation is expected to prevent land conversion in the villages around Buyan-Tamblingan lakes, as well as to maintain groundwater availability in the long run.